Effectiveness of Electroconvulsive Therapy for Refractory Status Epilepticus in Febrile Infection–Related Epilepsy Syndrome - Mirás Veiga, Alicia; Moreno, David Conejo; Menéndez, Ana Isabel Gómez; Siscart, Ignacio Muñoz; Fernández, Marta Del Olmo; Sánchez, Esteban Gómez; González, María García; Sáez, Fernando Gómez (Neuropediatrics, 2017)
Febrile infection–related epilepsy syndrome (FIRES) is a rare condition which evolves into refractory status epilepticus (SE), with poor outcome in most cases. Conventional antiepileptic drugs fail to control SE in FIRES patients. We report the case of a previously healthy 4-year-old boy who was diagnosed with FIRES. One week after pharyngitis and high fever he started seizures, followed by refractory SE. Benzodiazepines, phenytoin, high-dose barbiturates that induce burst suppression, high doses of corticosteroids, plasmapheresis, immunoglobulins, propofol, lidocaine, ketamine, inhaled desflurane, ketogenic diet, lacosamide, and therapeutic hypothermia were tried at different times in a period of 8 weeks, but all of them were ineffective. Electroconvulsive therapy (ECT) has been used in refractory SE in children. We report a case in which ECT was successfully used for treatment of refractory SE in a pediatric patient with FIRES syndrome.
Keywords: FIRES; children; status epilepticus; refractory; electroconvulsive therapy